Dosis de ceniza con cantidades uniformes de vacaza y su efecto en las características agronómicas y rendimiento forrajero del pasto Maralfalfa (pennisetum sp.) en Zungarococha – Perú – 2017 - Armas Vasquez, Emilio Martin (2018)
This research work was carried out in the project Vaccines of the Faculty of Agronomy (Fundo de Zungarococha), owned by the National University of the Peruvian Amazon entitled Ash dose with uniform amounts of cow and its effect on agronomic characteristics and forage performance of the Maralfalfa Grass (Pennisetum sp.) in Zungarococha - Peru - 2017. The evaluations were carried out at the ninth week after vegetative planting in bushes, in plots of 6 m2 of total area of 10.6 m2, established in an Ultisol soil. The design was Randomized Complete Blocks (DBCA), with five treatments and four repetitions, using the infostat statistical package, the treatments under study were: T0 (0 tons of ash / hectare), T1 (100 tons of ash / hectare), T2 (200 tons of ash / hectare), T3 (300 tons of ash / hectare) and T4 (400 tons of ash / hectare). According to the results obtained in the present investigation, the following conclusions were reached: Pennisetum sp. "Maralfalfa" had a positive response to the application of ash doses, being reflected in a higher forage yield in the higher doses. The best agronomic characteristics such as plant height, production of green matter and dry matter, were achieved by applying 400 kg of ash / Ha (T4), in the Pennisetum sp. "Maralfalfa." That the green matter yield was 39800.00 kg / hectare and 199000.00 kg / ha / year with the T4 (400 kg of ash / Ha).